PTU-181 An exploratory qualitative study investigating patients' experiences of constipation and how their self-reported symptoms and quality of life compare with currently available validated measures. (22nd June 2015) - Dimidi, E; Dibley, L; Cotterill, N; Knowles, CH; Scott, SM; Whelan, K; Norton, C
Abstract : Introduction: The most widely-used validated questionnaires for assessing constipation are the Patient Assessment of Constipation Symptoms (PAC-SYM) and the Cleveland Clinic Constipation Score (CCCS). We aimed to assess patients' reported symptoms of constipation, preferred terminology, and quality of life (QoL) issues, and whether these are reflected in currently available validated questionnaires. Method: Nineteen semi-structured interviews were conducted with patients presenting with constipation to assess their symptoms, the terminology they preferred, suitability of existing assessment tools, and to explore participants' constipation-related QoL issues. An inductive thematic framework was adopted to identify subthemes. Eleven clinicians rated the clinical importance of the symptoms and QoL issues reported by patients. Results: Three main themes were identified: a) language used to describe bowel issues, b) symptoms and toilet behaviours and c) issues regarding QoL. "Stool" and "motions" were the most acceptable words to describe stool, and "going to the toilet" for describing the act of defecation. The words "digital assistance", "evacuation" and "defecation" were poorly understood. Of the 12 most troublesome symptoms patients reported, only four are included in the PAC-SYM and five in the CCCS. Six of the symptoms reported as most troublesome are not included in either the PAC-SYM or the CCCS. Although all clinicians reported uncontrolled leakage of stool as a clinically important symptom, this was not included in either assessment tool. Of the symptoms that clinicians thought to be the most clinically relevant, two were not reported to be bothersome by patients (use of laxatives, straining). Only a small number of clinicians perceived some of the most bothersome symptoms reported by patients as clinically relevant. Conclusion: Patients presenting with constipation report a range of individual symptoms and QoL issues, most of which are not included in validated questionnaires. The terminology used in these questionnaires for describing bowel issues is poorly understood by patients. Furthermore, there is a discrepancy between patients and clinicians on what symptoms and QoL issues are perceived to be important. The development of a new assessment tool evaluating the wide range of constipation-related symptoms and QoL issues is needed. Disclosure of interest: E. Dimidi: None Declared, L. Dibley: None Declared, N. Cotterill Consultant for: Astellas Pharma Europe B. V. and Procter and Gamble, C. Knowles: None Declared, S. Scott: None Declared, K. Whelan: None Declared, C. Norton: None Declared.